KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM PEMBELAJARAN BERBASIS PROYEK BERINTEGRASI SCIENCE TECHNOLOGY ENGINEERING AND MATHEMATICS - Lies Indrawati; Mashudi Mashudi; Agung Hartoyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractLow achievement on High Order Thinking Skills (HOTS) of primary students in SDN 73 West Pontianak subistrict, had promoted the implementing of Science Technology Engineering and Mathematics (STEM) integrated project-based learning. The report is to describe how well HOTS achievement of 5th grade students in term of attitude, knowledge, skill, and the effect. A quantitative research with one group pertest posttest design was used along with observation, tests, and document studies. Data collection tools were transcripts from video recordings, student worksheets, and essay questions for the pretest and posttest which were analyzed using descriptive statistics and N Gain score. Mastery of HOTS in the domain attitude had an average score of 72 was in good category with a percentage of critical thinking aspect by 77%. The mastery of knowledge domain on process of transfer of C4 Level or analyzing had an average score of 70,37 or in a good category with a percentage of completeness by 56%. In skill domain for aspect of problem solving, the average score was 69,44 with a percentage of good categories by 66%. The effect of the implementation of STEM integrated project-based learning on high order thinking skills of 5th grade students of SD Negeri 73 was in moderate or quite influential categoryKeywords: High Order Thinking Skills (HOTS), Project-Based Learning, Science Technology Engineering And Mathematics (STEM) Integrated